2017
DOI: 10.33578/jpk-unri.v2i1.4459
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Bahan Ajar Berbasis E-Book Untuk Pembelajaran Kimia Sma Pokok Bahasan Struktur Atom

Abstract: This research aims to develop e-book based teaching materials for senior high school chemistry lesson at the subject of atomic structure. The research method used is research development. The research used Four D Model as a guide which is implemented in four stages are define, design, develop, and disseminate. This research is only up to the development stage. Research data were collected through assessment form filled by 4 validators, 2 material professional and 2 media professional. The result showed of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Furthermore, the assessment results by the media expert validator obtained an average total score of 89.6% or categorized as very valid. The e-module feasibility test is carried out so that researchers know how feasible this e-module can be used if the validator's assessment meets the percentage results ≥ 61% with valid to very valid categories (Asri & Dwiningsih, 2022;Maisarmah, 2022). Then the e-module is said to be suitable for use in the learning process.…”
Section: Validity Of E-modulementioning
confidence: 99%
“…Furthermore, the assessment results by the media expert validator obtained an average total score of 89.6% or categorized as very valid. The e-module feasibility test is carried out so that researchers know how feasible this e-module can be used if the validator's assessment meets the percentage results ≥ 61% with valid to very valid categories (Asri & Dwiningsih, 2022;Maisarmah, 2022). Then the e-module is said to be suitable for use in the learning process.…”
Section: Validity Of E-modulementioning
confidence: 99%
“…Several previous studies have shown that the use of a phenomenon-based learning approach has a positive impact on learning (Maisarmah, 2020). The first study stated that there was a significant difference between critical thinking skills and physics learning outcomes of students who were taught using a phenomenon-based learning model and students who were taught using conventional learning models (Pareken et al, 2015;Setyowati & Subali, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…With this paradigm, the existence of educators is no longer the only important factor in the learning process. The existence of educators can be replaced by learning materials in the form of modules, instructions, or educational software that can be used for independent learning by students (Azmi, 2015).…”
Section: Introductionmentioning
confidence: 99%